INDIAN PHILOSOPHY AND ITS SOCIAL CONCERNS: WITH SPECIAL REFERENCE TO THE CONCEPT OF DHARMA - Nayak, G C (Journal of Dharma, 2001)
While pondering over the topic in question, one is confronted, at the very outset, with a trend that condemns the entire orientation of Indian thought as other-worldly, a-social if not positively anti-social, and spiritual with a negative connotation that makes little room for material aspirations of man. A country that had the dignity and the pride of producing unique treatises like the Kama Sutra and Artha Sastra, apart from the entire Vedic tradition of "jivema saradah satam ", "pasyema saradah satam", the Upanishadic precepts like "kurvann-eveha karmani jijiviset satam samah", and the Vedic words of wisdom like "kevalagho bhavati kevaladi" or "bhunjante te tvagham papa ye pacantyatma karanat" of the Bhagavad Gita, to guide us in our day-to-day existence for living a long, meaningful life without being lost in one’s little ego, has been ironically branded as other worldly because of certain misconception regarding mukti or moksa as the highest ideal of man where one is to seek and find salvation for one’s own self alone with absolute indifference to social problem.